Performance upgrading of supercritical unit on preferable operation mode with promoting feed water temperature. (25th November 2022) - Wang, Yanhong; Zou, Zihong; Mao, Tianqin; Hu, Pengfei; Li, Xingcan; Wang, Xinnan
Highlights: Preferable operational strategy of supercritical unit is proposed under low loads. Model of steam temperature for on once through boiler is established. NOx emission and promoting economy under low loads are solved harmoniously. Decrease of 2.89 g/kWh and 37.3 MW increasing are achieved in economy of unit. Abstract: Promoting feed water temperature (FWT) at low loads for supercritical unit has proved to be an effective technology to ensure denitrification capacity of Selective Catalytic Reduction (SCR). However, operational economy of unit is significantly reduced on conventional intermediate point temperature (IPT) setting mode. Hence, a superior operation strategy defined as IPT regulating mode for supercritical unit is proposed. Mathematical method was further developed. Then, operation characteristics on economy and pollutant emission of a 660 MW supercritical unit are investigated on IPT regulating mode. A series of influencing mechanisms were revealed. Simultaneously, individual significant parameters were compared with that of traditional operation strategy. Results shows, supercritical unit with increasing FWT achieve a better performance on IPT regulating mode. Compared with traditional operation strategy, NOx emission are fully up to requirement. Concurrently about 2.89 g/kWh in standard coal consumption rate is decreased and 37.3 MW increasing in power generation is achieved averagely. Moreover, such operation strategy also makes superheated steam temperature maintain rated value. Reheated steam temperature promotes by 27.3 ℃ averagely, and become more smooth and steady. This study also reveals that advantages of proposed strategy will be more prominent with higher FWT and lower operating load.